2015
DOI: 10.1002/jps.24463
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Crystal Nucleation in Organic Solvents of Two Polymorphs of Curcumin

Abstract: Two crystal polymorphs of 1,7-bis-(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione (curcumin) have been obtained by crystallization from ethanol solution. The polymorphs have been characterized by DSC, IR spectroscopy and XRPD and shown to be the previously described forms I and III. The solubility of both polymorphs in ethanol and of one polymorph in ethyl acetate has been measured between 10°C and 50°C with a gravimetric method. Primary nucleation of curcumin from ethanol solution has been investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…Polymorphism of crystal structures of curcumin depends on the crystallization conditions. Curcumin crystals can adopt different shapes, such as monoclinic (acicular), orthorhombic (rice seed like), and amorphous (Liu, Svärd, Hippen, & Rasmuson, 2015;Mishra, Sanphui, Ramamurty, & Desiraju, 2014;Sanphui, Goud, Khandavilli, Bhanoth, & Nangia, 2011) Using scanning electron microscopy (SEM), to analyze curcumin particles, in our laboratory has revealed interesting morphological characteristics, that was dependent on the solvent in which curcumin was dispersed. Figure 2a presents a SEM image of the curcumin particles dispersed in methanol.…”
mentioning
confidence: 99%
“…Polymorphism of crystal structures of curcumin depends on the crystallization conditions. Curcumin crystals can adopt different shapes, such as monoclinic (acicular), orthorhombic (rice seed like), and amorphous (Liu, Svärd, Hippen, & Rasmuson, 2015;Mishra, Sanphui, Ramamurty, & Desiraju, 2014;Sanphui, Goud, Khandavilli, Bhanoth, & Nangia, 2011) Using scanning electron microscopy (SEM), to analyze curcumin particles, in our laboratory has revealed interesting morphological characteristics, that was dependent on the solvent in which curcumin was dispersed. Figure 2a presents a SEM image of the curcumin particles dispersed in methanol.…”
mentioning
confidence: 99%
“…1. [16][17][18][19][21][22][23][24] The solvents include polar protic, polar aprotic, and non-polar molecules, although the majority of the systems feature fairly polar solvents. The solutes differ significantly with regard to properties such as molar mass, the number of rotatable bonds, intermolecular interactions, and melting properties.…”
Section: Methodsmentioning
confidence: 99%
“…The solvent parameters are: molar mass (9); Reichardt polarity (10), which is an empirical polarity value; dynamic viscosity (11); density (12); boiling point (13); enthalpy of vaporisation (14); topological polar surface area (15); XLogP3 (16); molecular complexity (17); melting point (18); and refractive index (19). The solution parameters are: the number of solute-solvent hydrogen bonds (20) and the solid-liquid solubility (21).…”
Section: Initial Parameter Set -21 Parametersmentioning
confidence: 99%
“…The used separation methods were implemented as multi-step processes consisting of at least two successive sub-steps. It is reported that the main part of BDMC could be depleted after the first separation step, full removal was achieved after the second crystallization step [33,34]. DMC was always present in the final Studies show that CUR can be potentially used to treat over 25 diseases due to its anti-oxidative, immunosuppressive, wound-healing, anti-inflammatory and phototoxic effects [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, crystallization as a single separation technique was studied to purify CUR from the ternary mixture of curcuminoids [32][33][34]. Processes were described exploiting anti-solvent Crystals 2020, 10, 206 3 of 16 addition or system cooling, using methanol, ethanol and 2-propanol as process solvents and water as anti-solvent (Table 1).…”
Section: Introductionmentioning
confidence: 99%